Tumor antigens for cancer immunotherapy: therapeutic potential of xenogeneic DNA vaccines - Srinivasan Roopa; Wolchok Jedd D (Journal of Translational Medicine, 2004)
Abstract Preclinical animal studies have convincingly demonstrated that tumor immunity to self antigens can be actively induced and can translate into an effective anti-tumor response. Several of these observations are being tested in clinical trials. Immunization with xenogeneic DNA is an attractive approach to treat cancer since it generates T cell and antibody responses. When working in concert, these mechanisms may improve the efficacy of vaccines. The use of xenogeneic DNA in overcoming immune tolerance has been promising not only in inbred mice with transplanted tumors but also in outbred canines, which present with spontaneous tumors, as in the case of human. Use of this strategy also overcomes limitations seen in other types of cancer vaccines. Immunization against defined tumor antigens using a xenogeneic DNA vaccine is currently being tested in early phase clinical trials for the treatment of melanoma and prostate cancers, with proposed trials for breast cancer and Non-Hodgkin's Lymphoma.